Effects of sleep disruption and high fat intake on glucose metabolism in mice. (June 2016) - Ho, Jacqueline M.; Barf, R. Paulien; Opp, Mark R.
Highlights: Sleep fragmentation for 18-h per day reduces time in REMS and NREMS with dialy rebounds in REMS. NREMS rebound occurs only during the 24-h recovery period after 9 days of sleep fragmentation. Insulin sensitivity is sustained during sleep disruption and improves after recovery sleep. HFD-induced glucose intolerance during sleep disruption improves after recovery sleep. Abstract: Poor sleep quality or quantity impairs glycemic control and increases risk of disease under chronic conditions. Recovery sleep may offset adverse metabolic outcomes of accumulated sleep debt, but the extent to which this occurs is unclear. We examined whether recovery sleep improves glucose metabolism in mice subjected to prolonged sleep disruption, and whether high fat intake during sleep disruption exacerbates glycemic control. Adult male C57BL/6J mice were subjected to 18-h sleep fragmentation daily for 9 days, followed by 1 day of recovery. During sleep disruption, one group of mice was fed a high-fat diet (HFD) while another group was fed standard laboratory chow. Insulin sensitivity and glucose tolerance were assessed by insulin and glucose tolerance testing at baseline, after 3 and 7 days of sleep disruption, and at the end of the protocol after 24 h of undisturbed sleep opportunity (recovery). To characterize changes in sleep architecture that are associated with sleep debt and recovery, we quantified electroencephalogram (EEG) recordings during sleep fragmentation and recovery periods from an additional group of mice. We now report that 9 days of 18-h daily sleep fragmentation significantly reduces rapid eye movement sleep (REMS) and non-rapid eye movement sleep (NREMS). Mice respond with increases in REMS, but not NREMS, during the daily 6-h undisturbed sleep opportunity. However, both REMS and NREMS increase significantly during the 24-h recovery period. Although sleep disruption alone has no effect in this protocol, high fat feeding in combination with sleep disruption impairs glucose tolerance, effects that are reversed by recovery sleep. Insulin sensitivity modestly improves after 3 days of sleep fragmentation and after 24 h of recovery, with significantly greater improvements in mice exposed to HFD during sleep disruption. Improvements in both glucose tolerance and insulin sensitivity are associated with NREMS rebound, raising the possibility that this sleep phase contributes to restorative effects of recovery sleep on glycemic control.